Web-Based Design Of Vehicle Management Information System Of Widyatama University - Wahyu Wibowo, Ari Purno; Heryono, Heri; Hamdani, Dani (Brilliance: Research of Artificial Intelligence, 2024)
Vehicle inventory management and data collection information system is a system based on a Management Information System so that it has complete implementation functions that aim to record all vehicles. The main objective of developing this information system is to provide services that are faster, transparent and accurate on the service side of borrowing official vehicles within the Widyatama University environment. In the current vehicle inventory information system, it is not yet computerized and is done manually. The inventory registration information system is expected to be useful for minimizing errors that have occurred so far such as the unclear condition of the vehicle and when the vehicle will return, the design of the inventory information system is expected to produce an inventory information system that can work optimally and efficiently can perform testing services, readiness of drivers and management of motorized vehicles that operate according to the provisions that have been regulated, where the type of service can be adjusted to vehicle test data that is periodic, mutations in (Arrive) / out (booking) can be seen clearly by officers or users, other functions are there are changes to the function and status of the vehicle so that the vehicle will always be available and ready to be used.